Anthropogenic emissions from the combustion of composite coal-based fuels; Science of The Total Environment; Vol. 772 - Nikitin A. D. Aleksandr Dmitrievich; Nyashina G. S. Galina Sergeevna; Ryzhkov A. F. Aleksandr Fillipovich; Strizhak P. A. Pavel Alexandrovich (2021, 2021)
Title screen